KEWENANGAN KURATOR VENTRIS UNTUK MEWAKILI KEPENTINGAN ANAK DALAM KANDUNGAN JANDA DARI PERNIKAHAN SIRI PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 - EMELDA SAVIONITA (PREMISE LAW JURNAL, 2015)
A marriage can be divided into two; namely, a legal marriage according legal provisions and regulations and pernikahan siri, a marriage performed before the religious authorities but not registered by the State. The type of research was a judicial normative and analytical descriptive. Ventris curator has the authority to be the supporter or guardian of the child from the widow’s pregnancy of siri wedlock because the child’s status is considered equal in the legal position to the child from his mother’s pregnancy of legal marriage after the Ruling of the Constitutional Court No. 46/PUU-VIII/2010 is issued. BHP is given the authority to be the supporter and guardian to the fetius that is still in the widow’s pregnancy of pernikahan siri has the same authority of BHP toward the child in his mother’s pregnancy of a legal marriage, based on legal provisions, laws, and regulations on marriage. Keywords: Ventris Curator, Child, Pernikahan Siri